Formulation of herbal cream based on Ziziphus Mauritiana leaves extract and evaluation on physicochemical properties - Siti Umairah, Mokhtar; Ashviny, Murugan; Che Syahira, Che Awang (Penerbit Universiti Malaysia Pahang, 2020)
Plant derived substances and herbal medicines have recently attracted the great interest towards their versatile application, as medicinal plants used in traditional and modern medicine. The aim of the current study was to investigate the antioxidant activity of Ziziphus mauritiana leaves extract followed with the formulation of herbal creams based on ZM methanolic extract then evaluate the physical characteristic and stability of the creams. After the methanolic extract was obtained by using Soxhlet extraction, the extract was assessed for antioxidant activity by using stable 2,2- Diphenyl-1-picrylhydrazyl (DPPH) which showed the IC50 value of the ZM extract is 10.57 µg/ml, while IC50 value for ascorbic acid is 4.19 µg/ml. Four formulations of water in oil (w/o) emulsion based cream was formulated based on Ziziphus mauritiana leaves extract which are F1, F2, F3 and F4. Several physical properties were evaluated such as organoleptic, pH, viscosity, homogeneity, washability and emmolliency which proved that all formulations have good homogeneity, non greasy and under suitable pH and viscosity. Based on thermal stability test (45 °C ± 70 % RH, for 48 hours), it showed that F4 is not stable at high temperature compared to other formulations. Therefore, the present study indicated that the Ziziphus mauritiana leaves extract has great potential for personal care product development.